Family Planning Among Migrants Living in Adana - Kanat Şahin, Ceren; Demirbaş Üstün, Tuğba; Şenkaya, Ece; Kanlı, İlker; Küçüközkan, Mehmet Ali; Yerlikaya, Lütfullah; Kandemir, Mavisu; Yapıcı, Fadime; Al Dhelaa, Sakhr; Tekemen, Mert; Mete, Burak (Scientific Reports in Medicine, 2025)
Objective: Family planning plays a crucial role in public health by enabling individuals to control their reproductive choices in a responsible and informed manner. However, migrant populations often face barriers to accessing these services, leading to increased rates of unintended pregnancies and reproductive health complications. This study aims to assess the knowledge, attitudes, and behaviors regarding family planning among migrants living in Adana, Türkiye, compared to the local population.Methods: This cross-sectional study was conducted in January 2025 at Doğankent Family Health Center and Doğankent Migrant Health Center. The study population included individuals aged 15-49 who voluntarily participated. A structured questionnaire was administered through face-to-face interviews to collect sociodemographic data, knowledge levels, and usage patterns of modern family planning methods. The sample size was determined as 220 participants with 95% power and a 5% confidence interval; ultimately, data from 245 individuals were analyzed. Statistical analyses were performed using SPSS 20 software, employing the Kolmogorov-Smirnov test for normality assessment, parametric (t-test), non-parametric (Mann-Whitney U test), and categorical comparisons (chi-square test). A p-value of